A new model army: Emerging fish models to study the genomics of vertebrate Evo‐Devo. Issue 4 (11th August 2014) - Braasch, Ingo; Peterson, Samuel M.; Desvignes, Thomas; McCluskey, Braedan M.; Batzel, Peter; Postlethwait, John H.; Robinson‐Rechavi, Marc
ABSTRACT Many fields of biology—including vertebrate Evo‐Devo research—are facing an explosion of genomic and transcriptomic sequence information and a multitude of fish species are now swimming in this "genomic tsunami." Here, we first give an overview of recent developments in sequencing fish genomes and transcriptomes that identify properties of fish genomes requiring particular attention and propose strategies to overcome common challenges in fish genomics. We suggest that the generation of chromosome‐level genome assemblies—for which we introduce the term "chromonome"—should be a key component of genomic investigations in fish because they enable large‐scale conserved synteny analyses that inform orthology detection, a process critical for connectivity of genomes. Orthology calls in vertebrates, especially in teleost fish, are complicated by divergent evolution of gene repertoires and functions following two rounds of genome duplication in the ancestor of vertebrates and a third round at the base of teleost fish. Second, using examples of spotted gar, basal teleosts, zebrafish‐related cyprinids, cavefish, livebearers, icefish, and lobefin fish, we illustrate how next generation sequencing technologies liberate emerging fish systems from genomic ignorance and transform them into a new model army to answer longstanding questions on the genomic and developmental basis of their biodiversity. Finally, we discuss recent progress in the genetic toolbox for the major fish models for functional analysis, zebrafish, and medaka, that can be transferred to many other fish species to study in vivo the functional effect of evolutionary genomic change as Evo‐Devo research enters the postgenomic era. J. Exp. Zool. (Mol. Dev. Evol.) 324B: 316–341, 2015. © 2014 Wiley Periodicals, Inc.